Ethiopia’s Recovery from Crisis – Domains and Options (Seminar Slides) - Taffesse, Alemayehu Seyoum; Breisinger, Clemens (2023)
• Crisis situations- conflict, Covid-19 pandemic, Russia Ukraine war - loss of lives, displacement, disruption of economic activities, loss of livelihoods, food insecurity, loss of assets, etc. • Efforts aimed at rebuilding livelihoods must consider the most effective and efficient interventions • What are the available options? • Asset transfer programs have been shown to be effective in different settings • Evidence shows that livestock asset transfer programs have several development benefits – potentially suitable for reconstruction efforts